(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
This paper presents the software development for the ERT system used to monitor the static two phase (liquid/gas) flow for the application of a metallic bubble column wall. The software is developed using Graphical User Interface (GUI) application program in MATLAB. The software contains numerous functions to enable users to obtain the necessary information from the research. The animated projection of a single pair projection of the sensitivity distribution for a conducting boundary strategy, along with its weight balance map and normalised sensitivity map, can be viewed from the sensitivity distribution dropdown list. The images for the metal column with several phantoms using COMSOL simulation and experimental data can be viewed by clicking the construct image button in the GUI. The value for the assessment of the quality of each image is also displayed concurrently for each phantom selected.